Peroxisome proliferator‐activated receptor γ coactivator 1α regulates mitochondrial calcium homeostasis, sarcoplasmic reticulum stress, and cell death to mitigate skeletal muscle aging. Issue 5 (10th July 2019) - Gill, Jonathan F.; Delezie, Julien; Santos, Gesa; McGuirk, Shawn; Schnyder, Svenia; Frank, Stephan; Rausch, Martin; St‐Pierre, Julie; Handschin, Christoph
Abstract: Age‐related impairment of muscle function severely affects the health of an increasing elderly population. While causality and the underlying mechanisms remain poorly understood, exercise is an efficient intervention to blunt these aging effects. We thus investigated the role of the peroxisome proliferator‐activated receptor γ coactivator 1α (PGC‐1α), a potent regulator of mitochondrial function and exercise adaptation, in skeletal muscle during aging. We demonstrate that PGC‐1α overexpression improves mitochondrial dynamics and calcium buffering in an estrogen‐related receptor α‐dependent manner. Moreover, we show that sarcoplasmic reticulum stress is attenuated by PGC‐1α. As a result, PGC‐1α prevents tubular aggregate formation and cell death pathway activation in old muscle. Similarly, the pro‐apoptotic effects of ceramide and thapsigargin were blunted by PGC‐1α in muscle cells. Accordingly, mice with muscle‐specific gain‐of‐function and loss‐of‐function of PGC‐1α exhibit a delayed and premature aging phenotype, respectively. Together, our data reveal a key protective effect of PGC‐1α on muscle function and overall health span in aging. Abstract : In old muscle, a dysregulation of mitochondrial and sarcoplasmic calcium handling leads to cellular stress and death. Peroxisome proliferator‐activated receptor γ coactivator 1α, a key regulator of endurance exercise adaptation, can prevent these pathological events and mitigate muscle aging.